Numerical solution of the problem of fusion penetration of a metal layer under glass-to-metal welding conditions - Lyubimova, Olga Nikolaevna; Pestov, Konstantin Nikolaevich; Gridasova, Ekaterina Alexandrovna (Computational Continuum Mechanics, 2010)
We present a model and a method for numerical investigation of the problem of determining the depth of fusion zone in a metal cylinder under glass-to-metal welding conditions. The method is based on the inclusion of a specially constructed source term into the heat-conduction equation for a metal layer. The term describes the heat associated with phase transition and allows us to observe the moving boundary of the fused zone without using the classical Stefan condition. The results of calculations obtained by means of the proposed approach are given.
Keywords: heat conductivity; Stefan problem; fusion welding; numerical solution